Use of the Discovery Learning Model on Description Text reading Skills fo Class VII Students of SMP Negeri 2 Sungguminasa in Gowa District - Hanana Muliana (Universitas Muhammadiyah Enrekang, 2024)
This research aims to test the truth about the influence on the application of the Discovery Learning model in learning to read descriptive text in Class VII Students of SMP Negeri 2 Sungguminasa, Gowa Regency.The type of research is experimental research of the True Experiment type . The population in this research was Class VII students of SMP Negeri 2 Sungguminasa, Gowa Regency with a total of 42 people. Because the population studied was less than 100 students, in this study a total sample was used . This means that the entire population was sampled in this study, namely 42 samples. The sample in the study was grouped into two groups, namely 21 students in class VII.A as the control group/class and 21 students in class VII.B as the experimental group/class l. To obtain accurate data in this research, questions were used as research instruments. The data that has been collected is analyzed using descriptive techniques to describe the characteristics of the score distribution from the results of the control class and experimental class and inferential analysis techniques (experiments) using the t test analysis type to test the hypothesis. The calculation results are significant between the descriptive text reading skills of class VII students who use the Discoveri Learning model and students who do not use the Discoveri Learning model . This significant difference was proven based on the results of the t-test carried out on the posttest scores of the control and experimental groups with SPSS 20.0. The t-test results of the posttest scores for learning to read descriptive text for the control and experimental groups showed that tcount was 76.66 which was greater than ttable which was 51.42 with db 40. Keywords: Reading descriptive text, Experiment